Christopher Cairns: Pietro Aretino and thè Republic of Venice. Researches on Aretino and his Circle, 1527-1556. Olschki, Biblioteca dell' "Archivum Romanicum", serie I, vol. 194. Firenze, 1985. 269 p. - Larivaille, Paul (Revue Romane, 1986)
no abstr.